2019
DOI: 10.2147/dmso.s207596
|View full text |Cite
|
Sign up to set email alerts
|

<p>GLP-1 mediates the modulating effect of thymoquinone on feeding behaviors in diabetic rats</p>

Abstract: Background: Thymoquinone (TQ) is a safe nutrient isolated from the seeds or volatile oil extract of Nigella sativa . In addition to its benefits in glucose regulation, TQ improves feeding disorders in diabetic animals. Glucagon-like peptide-1 (GLP-1) analogs improve glycemic control and ameliorate obesity or hyperphagia. Therefore, the present study aimed to investigate the role of GLP-1 in TQ-induced anorexia. Method: Type 2 diabetes was induced in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Insulin secretion is affected by a variety of factors. NS can increase insulin secretion by increasing GLP1 secretion [46,47], stimulating beta-adrenergic receptors [48], proliferating and regenerating pancreatic beta cells [49,50], and decreasing serum glucagon [51,52]. In addition, black seed can increase the sensitivity of insulin receptors by increasing the production of p-IRS and p-AKT and decreasing leptin secretion [32,53].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin secretion is affected by a variety of factors. NS can increase insulin secretion by increasing GLP1 secretion [46,47], stimulating beta-adrenergic receptors [48], proliferating and regenerating pancreatic beta cells [49,50], and decreasing serum glucagon [51,52]. In addition, black seed can increase the sensitivity of insulin receptors by increasing the production of p-IRS and p-AKT and decreasing leptin secretion [32,53].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers reported that administration of 50 and 100 mg/kg/day of TQ could reduce the level of glucose, HOMA-IR, and food and water intake in diabetic rats. These effects of TQ were carried out through enhancing the endogenous level of glucagon-like peptide 1 ( Lee et al, 2019 ).…”
Section: The Effects Of Medicinal Plants On Metabolic Disordersmentioning
confidence: 99%
“…Thymoquinone being potent anticancer agent significantly lowers the hypoxia‐inducible factor‐1α (HIF‐1α) expression, inhibits interaction between HSP90 and HIF‐1α, and boosts HIF‐1α protein degradation in hypoxic cancer cells. It also suppresses the downstream genes of HIF‐1α, exhibited alterations in concentrations of lactate, glucose, and ATP levels, which further linked with disturbance of anaerobic metabolic and induction of apoptosis (Lee, Kuo, et al, 2019; Lee, Kim, et al, 2019). Thymoquinone also suppresses the cancer cell stages and the activation of PI3K/Akt pathway in oral squamous cell carcinoma (Ren & Luo, 2019).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Glucagon‐like peptide‐1 (GLP‐1) analogs have been found to improve the glycemic control, while administration of streptozotocin is used to induce the diabetes in experimental subjects. In diabetic rats, supplementation of thymoquinone by using oral route in dose‐dependent manner exhibited elevation in plasma GLP‐1 levels by lowering the hypergaphy (Harphoush et al., 2019; Lee et al, 2019; Lee, Kim, et al, 2019). In diet‐induced obesity mouse model, supplemented thymoquinone at the rate of 20 mg/kg BW per day prevented diabetic phenotype via lowering the glucose concentration, fasting insulins, serum cholesterol, triglycerides, and inflammatory markers resistin and MCP‐1, improving the glucose tolerance and insulin sensitivity, and enhancing the phosphorylated Akt level, whereas it phosphorylated SIRT‐1 in skeletal muscle and phosphorylated SIRT‐1 and AMPKα in liver (Shpetim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%